(untitled) (BIRDEM Medical Journal, 2023)
Follicular dendritic cells (FDC) are non-lymphoid, non-phagocytic, accessory immune cells, crucial for antigen presentation and regulation of the reactions in germinal centers. Sarcoma arising from FDC is very rare and it has low-to-intermediate malignant potential. Histopathological examination play a critical role for the diagnosis of the disease but in difficult cases immunohistochemistry has a great role and facilitates misinterpretation. Diagnosis of dendritic cell sarcoma (DCS) is a challenge for the histopathologists, because of its rare incidence and lack of familiarity of the histopathologists to see the slides. Here is a case of FDCS and the patient presented with left submandibular swelling. BIRDEM Med J 2023; 13(2): 111-115